Heat transfer performance characteristics of hybrid nanofluids as coolant in louvered fin automotive radiator - Sahoo R.R.; Sarkar J. (My University, 2025)
Present study deals with the enhancement of convective heat transfer performance of EG brine based various hybrid nanofluids i.e. Ag, Cu, SiC, CuO and TiO2 in 0–1% volume fraction of Al2O3 nanofluid, as coolants for louvered fin automobile radiator. The effects of nanoparticles combination and operating parameters on thermo physical properties, heat transfer, effectiveness, pumping power and performance index of hybrid nanofluids have been evaluated. Comparison of studied hybrid nanofluids based on radiator size and pumping power has been made as well. Among all studied hybrid nanofluids, 1% Ag hybrid nanofluid (0.5% Ag and 0.5% Al2O3) yields highest effectiveness and heat transfer rate as well as pumping power. However, SiC + Al2O3 dispersed hybrid nanofluid yields maximum performance index and hence this can be recommended for best coolant. For the same radiator size and heat transfer rate, pumping power increases by using Ag hybrid nanofluids leading to increase in engine thermal efficiency and hence reduction in engine fuel consumption. For same coolant flow rate and heat transfer rate, the radiator size reduces and pumping power increases by using Ag hybrid nanofluids leading to reduction in radiator size, weight and cost. © 2016, Springer-Verlag Berlin Heidelberg.